The influence of nutrition knowledge, Energy intake and family income level on the nutritional status of the elderly - Nora Rahmanindar; Seventina Nurul Hidayah; Andari, Istiqomah Dwi (Panakeia Journal of Epidemiology, 2025)
The elderly are an age group that is vulnerable to health problems, including nutritional problems, due to the physiological and socioeconomic changes that accompany the aging process. Poor nutritional status in the elderly can increase the risk of chronic diseases, reduce quality of life, and burden the family. Therefore, it is important to understand the factors that influence nutritional status in the elderly, especially in rural areas. This study aims to analyse the effect of nutritional knowledge, energy consumption, and family income level on the nutritional status of the elderly in Pagongan Village. The study used an observational method with a cross-sectional design and involved 40 elderly respondents who were purposively selected. Data on nutritional knowledge was obtained through a questionnaire, energy intake was calculated based on 24-hour recall, and nutritional status was measured using body mass index (BMI). Bivariate analysis was conducted using the Chi-Square test to determine the relationship between the independent variables and the nutritional status of the elderly. The results showed that there was a significant relationship between nutrition knowledge (p=0.043), energy consumption (p=0.012), and family income (p=0.001) with the nutritional status of the elderly. This study confirms the importance of proper nutrition education and family economic support in maintaining and improving the nutritional status of the elderly in rural communities